2008
DOI: 10.1186/1472-6874-8-17
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence among pregnant women in Rwanda

Abstract: BackgroundIntimate partner violence (IPV), defined as actual or threatened physical, sexual, psychological, and emotional abuse by current or former partners is a global public health concern. The prevalence and determinants of intimate partner violence (IPV) against pregnant women has not been described in Rwanda. A study was conducted to identify variables associated with IPV among Rwandan pregnant women.MethodsA convenient sample of 600 pregnant women attending antenatal clinics were administered a question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

26
143
4
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(175 citation statements)
references
References 40 publications
26
143
4
2
Order By: Relevance
“…This is consistent with the findings of previous studies 20,25,26 which showed that smoking, alcohol consumption, and using other substances of abuse were strongly associated with IPV. Substance abuse, including smoking and alcohol consumption, may be directly responsible for IPV by affecting cognition, reducing self-control, perpetuating aggression and may also induce stress and unhappiness in relationships, thereby, further increasing the risk of violence and conflict.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with the findings of previous studies 20,25,26 which showed that smoking, alcohol consumption, and using other substances of abuse were strongly associated with IPV. Substance abuse, including smoking and alcohol consumption, may be directly responsible for IPV by affecting cognition, reducing self-control, perpetuating aggression and may also induce stress and unhappiness in relationships, thereby, further increasing the risk of violence and conflict.…”
Section: Discussionsupporting
confidence: 93%
“…[19][20][21] Provision of education undoubtedly plays a protective role against IPV. Empowering women through social networking along with income earning improves their capacity to access information and resources available in society, and seek help in case of spousal abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Available estimates vary widely, from about 3% 15 to 30%, 1,[16][17][18] Most studies on prevalence have come from small clinical samples in maternity wards, 16 which often serve particular patient groups and communities, such as immigrant or minority groups, 19 rural communities, 20 adolescents, 21 and women from affluent areas. 22 A number of other studies include participants from rural and urban areas of the USA, 23 Canada, 24 Peru, 25 Mexico, 17 Rwanda, 26 Nigeria, 27 Saudi Arabia, 28 Iran, 16 as well as from India, 29 Pakistan, 30 UK, 15 and New Zealand. 31 Studies vary greatly in respect to the survey methods employed, which include face-to-face, telephone, computer-based and questionnaire interviews, which may affect response rates.…”
mentioning
confidence: 99%
“…Some studies ask about violence inflicted during pregnancy by any perpetrator, 24,30 while others focus solely on asking about violence by intimate partners. 31 Other factors which differ across research studies include the time periods explored; for example, some focus on intimate partner violence in any pregnancy, 31 some on the last pregnancy, 23 others in the previous year among pregnant women, 26 or at different time points during the pregnancy. 15,33 Additionally, data on the prevalence of intimate partner violence during pregnancy are often presented separately from data on other forms of intimate partner violence, making it difficult to discern if patterns are distinct.…”
mentioning
confidence: 99%
“…Alcohol use and household neglect resulting from it facilitate development of marital disharmony, relationship tension resulting in violence. 13 Prevalence of domestic violence was found to be more in respondents having no male child. Having no male child in the house led to perpetration of domestic violence as still there are beliefs such as male child is must for propagation of future generation and for economic purpose and support in old age.…”
Section: Discussionmentioning
confidence: 94%